The MIS 11-MIS 1 analogy, southern European vegetation, atmospheric methane and the 'early anthropogenic hypothesis' - Tzedakis, PC (COPERNICUS GESELLSCHAFT MBH, 2010)
Marine Isotope Stage (MIS) 11 has been considered a potential analogue for the Holocene and its future evolution. However, a dichotomy has emerged over the precise chronological alignment of the two intervals, with one solution favouring a synchronization of the precession signal and another of the obliquity signal. The two schemes lead to different implications over the natural length of the current interglacial and the underlying causes of the evolution of greenhouse gas concentrations. Here, the close coupling observed between changes in southern European tree populations and atmospheric methane concentrations in previous interglacials is used to evaluate the natural vs. anthropogenic contribution to Holocene methane emissions and assess the two alignment schemes. Comparison of the vegetation trends in MIS 1 and MIS 11 favours a precessional alignment, which would suggest that the Holocene is nearing the end of its natural course. This, combined with the divergence between methane concentrations and temperate tree populations after 5 kyr BP, provides some support for the notion that the Holocene methane trend may be anomalous compared to previous interglacials. In contrast, comparison of MIS 1 with MIS 19, which may represent a closer astronomical analogue than MIS 11, leads to substantially different conclusions on the projected natural duration of the current interglacial and the extent of the anthropogenic contribution to the Holocene methane budget. As answers vary with the choice of analogue, resolution of these issues using past interglacials remains elusive.